375 The changing nature of referral pathways for risk reducing salpingo-oophorectomy in a UK cancer centre. (13th November 2020) - Smallwood, K; Phillips, A; Asher, V; Crockett, S; Huang, V
Abstract : Introduction: In 2013 the National Institute of Clinical Excellence (NICE) released guidance changing the threshold for BRCA testing from a lifetime risk of 20% to 10%. In 2015 NHS England brought this change into practice. Previously the majority of women were referred based on family history alone. This study will demonstrate how this evidence has changed when and how women are referred for risk management in our hospital. Methods: A retrospective study of 274 patients referred to the family history clinic for consideration of risk reducing surgery between January 2009 and December 2018 at the Royal Derby Hospital. Results: The number of referrals made in 2013 and 2014 were double those made in 2012 however this trend did not continue. Prior to 2015 69% of referrals were based on family history alone, compared to 34% after 2015. In 2018 all women undergoing risk reducing surgery had a genetic diagnosis, compared to 30% in 2009. Median age at surgery has reduced from 50 in 2009, to 43 in 2018. Conclusion: There has been no significant increase in referrals despite a lower threshold for BRCA testing. Women not previously eligible for testing were still offered surgery based on family history alone. Genetic diagnosis has allowed more accurate risk assessment and enables us to counsel women appropriately. Salpingo-oophorectomy reduces ovarian cancer risk from up to 50% to around 1%. Women are now being diagnosed with the BRCA gene at a younger age which is reflected in the fall in median age at surgery.